Epstein-Barr Virus and Multiple Sclerosis: Unraveling the Complex Relationship - Ling Zhong; Qinjian Zhao; Xiao Zhang (Medical Research and Its Applications Vol. 5, 2024)
The present study primarily focuses on Epstein-Barr Virus and Multiple Sclerosis. Epstein-Barr virus (EBV) infection is the leading cause of Multiple sclerosis (MS), a chronic inflammatory disease. Globally, MS affects approximately 2.8 million individuals, resulting in significant economic burdens due to treatment expenses and patient unemployment. The association between EBV and MS is supported by various studies encompassing epidemiological, immunological, and virological aspects. These studies revealed higher EBV levels in MS patients, expression of EBV proteins within MS lesions, and the elevation of specific immunological markers following EBV infection. Although the precise mechanism through which EBV initiates MS remains unclear, evidence suggests a phenomenon called molecular mimicry, wherein the immune system’s response to EBV may mistakenly target neuronal tissue. Efforts are underway to develop therapies targeting this relationship, such as EBV-specific cytotoxic T-cell therapy. It is clear from multiple verified studies that EBV, as a precipitating factor, significantly influences MS progression. Consequently, EBV is a promising focus for the development of future treatments or preventative measures for MS. Nevertheless, the exact mechanism underlying EBV-induced MS and the potential for prophylactic vaccines continue to be subjects of ongoing research.